2019
DOI: 10.1116/1.5054101
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and kinetic modeling of the ion energy distribution function at the substrate surface during magnetron sputtering of silver targets in radio frequency argon plasmas

Abstract: The quality of the films obtained by magnetron sputtering depends on numerous parameters, including the energy of the ions impinging on the substrate. The energy distribution functions of Ar and Ag ions during magnetron sputtering of a silver target in rf argon plasmas are hereby reported. Measurements were carried out by plasma sampling mass spectrometry at (i) various bias voltages on the surface of the target at constant pressure and (ii) various operating pressures at constant bias voltage. A distinct high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…During deposition of film using magnetron sputtering, the energy of an ion incident on a substrate surface has a strong influence on the growth and properties of the film, such as the microstructure, crystallography, phase composition, and mechanical and optical properties. Therefore, to understand the mechanism of film growth, the ion energy at the substrate surface is of great interest [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…During deposition of film using magnetron sputtering, the energy of an ion incident on a substrate surface has a strong influence on the growth and properties of the film, such as the microstructure, crystallography, phase composition, and mechanical and optical properties. Therefore, to understand the mechanism of film growth, the ion energy at the substrate surface is of great interest [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the model of the ion energy distribution at the substrate surface in radio-frequency (RF) magnetron sputtering developed by Garofano et al [1], the energy of an ion incident on the substrate surface was related to the ejection of atoms from the target, their transport in the gas phase, and their acceleration in the sheath near the surface of the substrate [1]. However, for magnetron sputtering, near the target surface, there existed an electric field pointing toward the target, which resulted from the self-bias voltage [2,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Ar ions impinging the target can be neutralized and reflected with high kinetic energies. [1][2][3][4][5][6][7][8][9][10] These neutral atoms can become entrapped in the deposited film. It has been reported that the amount of gas entrapped in a deposited film increases with increasing targetto-gas atomic mass ratio.…”
mentioning
confidence: 99%